Decoding foot deformity and joint-destruction pathways in diabetes: Emerging insights from in-vivo foot joint kinetic measures. (December 2022) - Deschamps, Kevin; Staes, Filip; Nobels, Frank; Bus, Sicco A.; Armstrong, David G.; Matricali, Giovanni
Abstract: Background: A comprehensive insight into the effect of longstanding diabetes mellitus and neuropathy on foot joint kinetics during walking is lacking. Our goal was to assess the in-vivo kinetics of major foot joints in persons with diabetes. Methods: Three groups, matched for age, sex and walking speed were recruited in this study: 1) people with diabetic peripheral neuropathy, 2) people with diabetes without peripheral neuropathy, and 3) control subjects without diabetes. Participants were instrumented with retroreflective markers on both feet and lower limbs and underwent a barefoot gait analysis using a state-of-the-art multi-segment kinetic foot modelling approach in order to provide accurate joint loading measures at the ankle, midtarsal, tarso-metatarsal and hallux joints. Findings: The group with neuropathy showed reduced ankle peak plantarflexion angular velocity compared to the control group ( P  = 0.002). Both groups with diabetes showed a significantly reduced midtarsal peak plantarflexion angular velocity, peak power generation and positive work compared to the control group ( p  < 0.01). Groups showed significant differences with respect to the tarsometatarsal peak dorsiflexion ( p  = 0.006) and plantarflexion angular velocity ( P  < 0.05). Interpretation: This study shows that both diabetes groups have similar joint loading and power absorption capacity but seem to lose their power generation capacity especially at the midtarsal joint. This loss of power generation capacity and the resulting decreased net mechanical work of the foot potentially embodies a foot that poorly supplements the body's mechanical energy during push-off. This phenomenon may cause excessive tissue stresses that contribute to foot deformity and joint-destruction mechanisms. Highlights: Persons with diabetes mellitus had decreased sagittal angular velocity throughout foot segments. Decreased angular velocity contributed to reduced midtarsal power generation. Persons with diabetic neuropathy tend to acquire an energy neutral foot.